Prospective study investigating hypofractionated proton beam therapy in patients with inoperable early stage non-small cell lung cancer - Yang, Kyungmi; Noh, Jae Myoung; Park, Hye Yun; Yoo, Hongseok; Shin, Sun Hye; Pyo, Hongryull (Frontiers in Oncology, 2024)
To report the results of hypofractionated proton beam therapy (PBT) for the treatment of early stage lung cancer in patients not suitable for surgical resection.Methods: Data from 27 adult patients, who were diagnosed with inoperable cT1-3N0 non-small cell lung cancer (NSCLC) between March 2018 and August 2020, were analyzed. PBT was prescribed as 64 Cobalt Grey equivalents delivered in 8 fractions (Sumitomo, Japan). The primary endpoint was local control; secondary endpoints included overall survival, quality of life, and grade ≥3 toxicity.The median follow-up was 28.9 months (range, 1.1-62.1 months). During follow-up, 13 (48.1%) patients experienced disease progression, including local progression in 7. Two-year local control rates were 73.5%, 85.7% for T1, and 61.4% for T2-3. The worse local control rate was observed in those with large clinical target volumes (≥47.5 cc) and heavy smoking history (≥30 packyears). The two-year overall survival rate was 76.5%. Grade 3 radiation-related toxicities were observed in 2 (7.4%) patients. In the European Organization for Research and Treatment of Cancer Quality of Life Core 30 results, the global score did not change significantly from baseline. However, dyspnea score increased from 19.8 before PBT to 33.3 at 4 months' post-PBT (p=0.047) and was maintained until 13 months (p=0.028).Hypofractionated PBT was a safe treatment option for inoperable early stage NSCLC and appeared to be appropriate for small tumor volumes. However, local control for larger tumors requires further improvement.